Congestion Charges in Mega Cities: On Affection and Effectiveness - Yuan, Yanhong; Li, Guomin; Zhang, Rongxia; Li, Wei; Fan, Qingqing (Journal of Environmental Accounting and Management, 2026)
Implementing congestion charges is a method that large cities in China are considering to employ as a solution to the growing traffic congestion problem in recent years. The purpose of this paper is to make a comprehensive prediction and analysis of the effect and impact of the policy. The system dynamics model of traffic congestion charge is established based on five main factors, such as per capita income, population, GDP, private car ownership and air sulfur dioxide content. In the model, the population loss measures peoples’ bearing of the policy and the amount of private car travel measures policy effects. The results show that after the implementation of the scheme is stable, private car travel volumes will decrease significantly and keep growing. This shows that congestion charging scheme can effectively control congestion, and will not have a significant impact on car demand. In addition, the high toll price will have a significantly negative impact on the low-income population, so it is vital that a moderate congestion toll price is fixed.